Early light curves for Type Ia supernova explosion models - Noebauer, Ulrich; Kromer, Markus (Monthly notices of the Royal Astronomical Society, 2017)
Upcoming high-cadence transient survey programmes will produce a wealth of observational data for Type Ia supernovae. These data sets will contain numerous events detected very early in their evolution, shortly after explosion. Here, we present synthetic light curves, calculated with the radiation hydrodynamical approach STELLA for a number of different explosion models, specifically focusing on these first few days after explosion. We show that overall the early light curve evolution is similar for most of the investigated models.